2022
DOI: 10.3390/biom13010035
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Consequences of Single Social Defeat on Accumbal Dopamine and Behaviors in Rats

Abstract: The present study aimed to explore the consequences of a single exposure to a social defeat on dopamine release in the rat nucleus accumbens measured with a fast-scan cyclic voltammetry. We found that 24 h after a social defeat, accumbal dopamine responses, evoked by a high frequency electrical stimulation of the ventral tegmental area, were more profound in socially defeated rats in comparison with non-defeated control animals. The enhanced dopamine release was associated with the prolonged immobility time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…While these results resemble the effects of defeat in the signaling pathway, it is worth noting that CREB and the MAPK pathway are also regulated by systems previously reported to respond to social defeat. For instance, social defeat elicits increased dopamine release in the NAc ( Tidey and Miczek, 1996 ; Nemets et al, 2022 ), and dopamine receptors are known to affect MAPK and CREB phosphorylation ( Wang H. et al, 2018 ). Therefore, future studies should explore cell-specific changes in the NAc driving the observed changes in these markers.…”
Section: Discussionmentioning
confidence: 99%
“…While these results resemble the effects of defeat in the signaling pathway, it is worth noting that CREB and the MAPK pathway are also regulated by systems previously reported to respond to social defeat. For instance, social defeat elicits increased dopamine release in the NAc ( Tidey and Miczek, 1996 ; Nemets et al, 2022 ), and dopamine receptors are known to affect MAPK and CREB phosphorylation ( Wang H. et al, 2018 ). Therefore, future studies should explore cell-specific changes in the NAc driving the observed changes in these markers.…”
Section: Discussionmentioning
confidence: 99%